CAN LIBERTARIANS GET AWAY WITH FRAUD?. (10th January 2018) - Ferguson, Benjamin
Abstract: In this paper I argue that libertarianism neither prohibits exchanges in which consent is gained through deceit, nor does it entail that such exchanges are morally invalid. However, contra James Child's (1994) similar claim, that it is incapable of delivering these verdicts, I argue that libertarians can claim that exchanges involving deceitfully obtained consent are morally invalid by appealing to an external theory of moral permissibility.